Nye processioner som udtryk for gamle religionsmønstre - Johansen, Kirstine Helboe (Religionsvidenskabeligt tidsskrift, 2017)
This article analyzes two examples of new processions in the Evangelical-Lutheran Church in Denmark, observed in the context of Halloween Services and Baby Hymn Singing activities. These two cases are analyzed from theoretical perspectives that connect approaches from sociology of religion within the study of contemporary religion (McGuire 2002; Ammerman 2016) with history of religion perspectives on the understanding and development of religious rituals (Bellah 1964; Rappaport 1999). Based on this analysis, the article discusses how to understand these re-emerging processions in a contemporary context and argues for a greater focus on the religious didactic dimensions of processions.